2005
DOI: 10.1111/j.1467-9817.2005.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual stress in adults with and without dyslexia

Abstract: The relationship between dyslexia and visual stress (sometimes known as MearesIrlen syndrome) is uncertain. While some theorists have hypothesised an aetiological link between the two conditions, mediated by the magnocellular visual system, at the present time the predominant theories of dyslexia and visual stress see them as distinct, unrelated conditions, a view that has received some support from studies with children. Studies of visual stress in adults are rare, yet recent reports of a high incidence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 61 publications
5
59
1
1
Order By: Relevance
“…These results support the previous research demonstrating colored overlays have little effect on reading fluency (e.g., Ritchie et al 2011). Further, whereas previous research has suggested that colored overlays have greater effect on children with dyslexia than adults (Singleton and Trotter 2005;Singleton and Henderson 2007), this study suggests that colored overlays may have a deleterious effect on adults. Although colored overlays did not improve reading fluency for the children in this study, the adult's performance actually worsened with the colored overlay intervention.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…These results support the previous research demonstrating colored overlays have little effect on reading fluency (e.g., Ritchie et al 2011). Further, whereas previous research has suggested that colored overlays have greater effect on children with dyslexia than adults (Singleton and Trotter 2005;Singleton and Henderson 2007), this study suggests that colored overlays may have a deleterious effect on adults. Although colored overlays did not improve reading fluency for the children in this study, the adult's performance actually worsened with the colored overlay intervention.…”
Section: Discussionsupporting
confidence: 39%
“…Colored overlays are claimed to alleviate visual stress and improve symptoms commonly related to dyslexia such as low reading rate, accuracy, and comprehension (Evans et al 1999;Rickelman & Henk, 1990; BWhat is Irlen Syndrome,n .d.). This claim may be because visual stress often co-occurs with dyslexia (Singleton and Trotter 2005;Singleton and Henderson 2007). Colored overlays have become so common, they are now considered an approved accommodation for standardized tests in several states including California, New Mexico, Massachusetts, Nevada, and Oklahoma (BPublished Research,^n.d.,para.1).…”
Section: Introductionmentioning
confidence: 99%
“…This statement is supported by both single masked clinical trials (Bouldoukian et al, 2002;Evans and Joseph, 2002;Kriss, 2002;Kriss andEvans, 2005, Singleton andHenderson, 2007;Singleton and Trotter, 2005;Swanson et al, 1993;Wilkins et al, 2001) and also by double-masked randomised placebo-controlled trials (Robinson and Foreman, 1999a, b;Wilkins et al, , 2002, in which filters of similar colour were offered as control. Additionally, a recent experiment studied reading speed at a large range of chromaticities and thereby directly addressed the issue of the precision with which the coloured filters need to be prescribed so as to suit an individual .…”
Section: Individual Differences In Colourmentioning
confidence: 82%
“…Indeed, a previous study has suggested that blue and bluish-green overlays (which exclude long-wavelength light) facilitate reading [30]; however, the most beneficial overlay color has been found to vary among individuals [5,8,22,23,31]. While the source of between-individual variation remains unclear [32], studies have investigated which colors are most beneficial to patients with MIS.…”
Section: Effect Of Color On Meares-irlen Syndromementioning
confidence: 98%